Fibrosarcoma of the chest wall: A case report - Kabir, SF (Pulse, 2011)
An 85 year old man presented with a large swelling over the right side of the chest wall of 3 years duration. Patient had no complaints other than a swelling which looked aggressive. On the 1st instance it looked malignant. Histopathology of the specimen confirmed that it is a case of fibrosarcoma. Excision of the tumor done with 2cm healthy margin and the patient was referred to radiotherapist for possible adjuvant therapy. DOI: http://dx.doi.org/10.3329/pulse.v4i1.6962 Pulse Vol.4 January 2010 p.30-31